RELATIONSHIP BETWEEN PHYSICAL HOUSING CONDITION AND BEHAVIORAL WITH PNEUMONIA INCIDENCE IN UNDER FIVE YEAR OLD CHILDREN IN THE WORKING AREA OF PUBLIC HEALTH CENTER YOSOMULYO METRO CITY - Ayu Tri Darmawati; Elvi Sunarsih; Inoy Trisnaini (Faculty of Public Health, Sriwijaya University, 2016)
Background: Pneumonia is a health problem that is a major cause of death of children under five years. The cause of pneumonia can be caused by environmental factors in the home that includes a physical home environment and behavioral factors. Based on data from the Health Center Metro Yosomulyo increased cases of pneumonia for three consecutive years. Yosomulyo Health Center is a health center that ranks first pneumonia cases highest in Metro City.The aim of study is analyze relationship between physical housing condition and behavioral with pneumonia incidence Method: This study used a case control study design. The sample in this study were 108 samples with a ratio of 1: 3, which consisted of 27 cases of pneumonia and 81 control cases in the immediate neighborhood. Data analysis was performed using univariate, bivariate and multivariate. Result: The results of the bivariate analysis is known that there are eight independent variables associated with the incidence of pneumonia in children under five is ventilation, humidity, lighting, temperature, mother's education, presence of family members who smoke, habit of opening window and house cleaning habits. Chi square all <0,05 and multiple logistic regression test custom variable opening the window is the most dominant variable incidence of pneumonia in children under five. Conclusion: Opening the window is a variable habit most dominant related events pneumonia with the toddler in the working area of public health center Yosomulyo Metro City.